2013
DOI: 10.1016/j.bbamcr.2013.02.016
|View full text |Cite
|
Sign up to set email alerts
|

p70S6 kinase is a target of the novel proteasome inhibitor 3,3′-diamino-4′-methoxyflavone during apoptosis in human myeloid tumor cells

Abstract: Acute myeloid leukemia (AML) is a deadly disease characterized by the clonal expansion and accumulation of hematopoietic stem cells arrested at various stages of development. Clinical research efforts are currently focusing on targeted therapies that induce apoptosis in AML cells. Herein, the effects and mechanisms of the novel flavone 3,3'-diamino-4'-methoxyflavone (DD1) on AML cell dysfunction were investigated in AML cells (monoblast U937, myelomonocyte OCI-AML3, promyelocyte NB4, myeloblast HL-60) and bloo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 77 publications
(109 reference statements)
3
12
0
Order By: Relevance
“…Dhar et al showed that cisplatin caused a caspase-3-dependent cleavage of p70S6K and that proteolytic cleavage is important for cisplatin-induced apoptosis in H69 and A549 colon cancer cells [32]. Also, the flavone 3,3 -diamino-4 -methoxyflavone (DD1) inhibited cellular proliferation and induced apoptotic cell death in several acute myeloid leukemia cell lines associated with caspase proteolytic cleavage of p70S6K [51]. The exact molecular mechanism through which these anticancer drugs specifically targets p70S6K to caspase-dependent cleavage remain unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Dhar et al showed that cisplatin caused a caspase-3-dependent cleavage of p70S6K and that proteolytic cleavage is important for cisplatin-induced apoptosis in H69 and A549 colon cancer cells [32]. Also, the flavone 3,3 -diamino-4 -methoxyflavone (DD1) inhibited cellular proliferation and induced apoptotic cell death in several acute myeloid leukemia cell lines associated with caspase proteolytic cleavage of p70S6K [51]. The exact molecular mechanism through which these anticancer drugs specifically targets p70S6K to caspase-dependent cleavage remain unknown.…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, the expression of RPS6KB1 mRNA was not affected by EAA or glucose infusion. A cause for this discrepancy may relate to degradation of the S6K1 protein when apoptosis is activated (Dhar et al, 2009;Piedfer et al, 2013).…”
Section: Mammary Mtorc1 Response Does Not Explain Changes In Milk Promentioning
confidence: 99%
“…All these natural proteasome inhibitors display proapoptotic properties [71][72][73]. It is noteworthy that resveratrol, curcumin, apigenin, quercetin and EGCG induce CLL cell apoptosis (see below) as does the synthetic diaminomethoxyflavone [74] that we have recently shown to be a proteasome inhibitor [75]. It is therefore possible that these compounds activate CLL cell apoptosis at least partly through the inhibition of proteasomal degradation.…”
Section: Plant-derived Proteasome Inhibitorsmentioning
confidence: 99%